Influence of different reciprocating systems on the apical extrusion of debris in flat-oval canals - Monique Marchiori; Arissa Michelle Yamada Corrêa; Flávia Sens Fagundes Tomazinho; Marilisa Carneiro Leão Gabardo; Natanael Henrique Ribeiro Mattos; Luiz Fernando Fariniuk; Flares Baratto-Filho (Universidade Estadual de Campinas, 2021)
Aim: To evaluate the apical extrusion of debris in flat-oval canals, using three reciprocating systems at two different working lengths (WL), 0 mm and 1 mm from the apical foramen. Methods: Ninety mandibular incisors were randomly divided into three groups based on the systems: WaveOne Gold #25.07 (WOG), ProDesign R #25.06 (PDR), and X1 Blue #25.06 (X1B). Extruded debris were collected and dried in pre-weighed Eppendorf tubes. Three consecutive weighings were performed for each tube, and the mean was calculated. If the assumptions of normality and homogeneity of variance were not met, the Kruskal-Wallis test was used to analyze the amount of extruded debris between groups with the same WL, and the Mann-Whitney U test was used for comparison within groups for each WL. Results: All groups had extruded debris, with higher median values occurring at 1 mm. No significant difference regarding the amount of debris extrusion was observed at 0 mm (p>0.05) and 1 mm (p>0.05) between groups. However, within the groups, at different WL, there was greater extrusion at 1 mm (p<0.05), with PDR differing significantly from the other systems (p<0.05). Conclusion: The extrusion of debris occurred regardless of the group, with higher values at 1 mm. However, using PDR at 1 mm from the apical foramen showed the highest values of extrusion.